2022
DOI: 10.1212/wnl.0000000000200986
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Screening for Spinal Muscular Atrophy in New York State

Abstract: Background and Objectives:Spinal muscular atrophy (SMA) was added to the Recommended Uniform Screening Panel (RUSP) in July 2018, largely on the basis of the availability and efficacy of newly-approved disease modifying therapies. New York State (NYS) started universal newborn screening for SMA in October 2018. The authors report the findings from the first 3 years of screening.Methods:Statewide neonatal screening was conducted using DNA extracted from dried blood spots using a real-time quantitative polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 34 publications
5
37
0
Order By: Relevance
“…In our study, most parents of children with 2 or 3 copies of the SMN2 gene were in favor of treatment with onasemnogene abeparvovec. Similar experiences have been reported by other research groups [ 24, 27 ]. However, a proportion of parents prefer RNA-based therapy mainly because of what they perceive as the unclear risk of gene replacement therapy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, most parents of children with 2 or 3 copies of the SMN2 gene were in favor of treatment with onasemnogene abeparvovec. Similar experiences have been reported by other research groups [ 24, 27 ]. However, a proportion of parents prefer RNA-based therapy mainly because of what they perceive as the unclear risk of gene replacement therapy.…”
Section: Discussionsupporting
confidence: 92%
“…Depending on the structures in place in different countries, the time to notify families of the suspicious finding varied from 8 to 11 days after birth. The median start of treatment in patients with 2 or 3 SMN2 copies varied from 19 days after birth in our pilot study to 34 days [19,24]. Knowing that at the time of the first clinical examination, up to one third of patients already show the first symptoms of SMA [19,25], shortening this period is an important goal.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Copy number analysis for SMN1 and SMN2 genes associated with SMA can be difficult, as the copy number of these varies much more than other regions within the genome. Furthermore, rapid turnaround time for SMA diagnostic testing is important for timely administration of therapies which halt neuron degeneration [ 15 , 16 ]. SMA genetic testing for SMN1 and SMN2 exon 7 copy numbers is accomplished using a variety of methods, including PCR followed by capillary electrophoresis (PCR/CE), quantitative PCR (qPCR), digital droplet PCR (ddPCR), multiplex ligation-dependent probe amplification (MLPA), and next-generation sequencing (NGS).…”
Section: Sma Diagnostic and Carrier Screening Testingmentioning
confidence: 99%
“…When positive screening results are identified, follow-up testing is performed to confirm diagnosis and obtain SMN2 copy number results to infer disease prognosis. However, recent studies have provided data supporting the reporting of SMN2 copy numbers along with initial screening results, as it is beneficial for SMA patients with two copies of SMN2 where treatment timing is most crucial [ 16 ]. Others have suggested that disease modifier variant testing is also important to further refine the likely prognosis for SMA patients identified through NBS with two or three copies of SMN2 [ 17 ].…”
Section: Newborn Screening For Smamentioning
confidence: 99%